Relevansi Nilai-Nilai Peradaban Islam dalam Proses Modernisasi Ilmu Pengetahuan, Sains, Teknologi, Seni dan Budaya - ridwan hidayah; Neneng Nurhasanah; Astrid Rizkya Annisa Salendari (Jurnal Hukum Lex Generalis, 2026)
The modernization of science, technology, arts, and culture has generated various social phenomena, including shifts in moral values, the misuse of technology, ethical challenges, and the growing need for policies that ensure the responsible use of innovation. These conditions indicate that scientific and technological advancement requires not only continuous innovation but also a value-based framework capable of balancing progress with public welfare. This study aims to analyze the relevance of Islamic civilization values in responding to the social phenomena resulting from modernization and to examine their contribution to policy development in the fields of science, technology, arts, and culture. This research employs a normative legal research method using conceptual, statutory, and historical approaches. Legal materials were collected through library research and analyzed using a descriptive-qualitative method. The findings reveal that the principles of tawhid (monotheism), justice, trustworthiness (amanah), and public benefit (maslahah) remain relevant as ethical foundations for scientific development and public policymaking. The novelty of this study lies in integrating the analysis of social phenomena, public policy, and Islamic civilization values within a legal framework, thereby providing a conceptual basis for developing regulations and educational policies that are adaptive to modernization while preserving humanity, justice, and sustainability.